Strong piezoelectricity in [H-beta-(2-pyridyl)-Ala-OH][BF4] and [H-beta-(2-pyridyl)-Ala-OH][ClO4] - new amino acid based hybrid crystals - Wojtas, Maciej
New amino acid based [H-beta-(2-pyridyl)-Ala-OH][ClO4] and [H-beta-(2-pyridyl)-Ala-OH][BF4] crystals were synthesized and their structure and functional piezoelectric properties were investigated in detail. The former crystallizes in the piezoelectric P2(1)2(1)2(1) space group whereas the latter belongs to the polar P1 space group. Piezoelectric force microscopy (PFM) measurements revealed that the piezoelectric coefficient, d(15)eff, of the [H-beta-(2-pyridyl)-Ala-OH][BF4] crystal is more than twice that in the widely used transducer material lithium niobate, LiNbO3. The crystal structures of both [H-beta-(2-pyridyl)-Ala-OH] derivatives are characterized by inter-and intramolecular hydrogen bond networks that are responsible for a high piezoresponse. The existence of intramolecular hydrogen bonding was confirmed by means of IR measurements. The thermogravimetric (TGA) technique was applied to study the thermal behavior of the title crystals. The piezoelectric properties are discussed in the context of the crystallographic structure and the microstructure of these crystals.